(untitled) (JOISCO: Journal of Islamic Communication, 2026)
This study aims to uncover the values ​​of local wisdom contained in the saprahan tradition in the Sambas Malay community, as a form of cultural communication that strengthens togetherness and social identity. The researcher used a qualitative research type with a descriptive approach. Primary data were obtained through observations and direct experiences of the researcher in the implementation of the Saprahan tradition, while secondary data were obtained from related literature and documentation. Data analysis techniques were carried out interactively through the process of reduction, presentation, and drawing conclusions. The results of the study indicate that the Saprahan tradition contains local wisdom values, including the meaning of the six pillars of faith from the division of groups of six people, the symbol of togetherness from the elongated and facing sitting position, respect for guests through sitting on a saprah cloth or banana leaf, the spiritual value of the five food menus and sherbet water that symbolize the five pillars of Islam, and respect for food through the habit of eating with hands. This tradition reflects the philosophy of "sitting at the same low, standing at the same height" as a form of equality and togetherness in the social interactions of the Sambas Malay community.